2023
DOI: 10.1039/d3nr00403a
|View full text |Cite
|
Sign up to set email alerts
|

Computational investigation on lipid bilayer disruption induced by amphiphilic Janus nanoparticles: combined effect of Janus balance and charged lipid concentration

Danh Nguyen,
James Wu,
Patrick Corrigan
et al.

Abstract: Janus nanoparticles (NPs) with charged/hydrophobic compartments have garnered attention for their potential antimicrobial activity. These NPs have been shown to disrupt lipid bilayers in experimental studies, yet the underlying mechanisms...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Second, characterization of Janus structures at the <50 nm regime that occurs due to anisotropic surface chemistry and anisotropic functionalization is challenging due to the requirements of sophisticated chemical characterization at such length scales. Third, cellular interaction with Janus nanostructures is not well understood, and recent studies indicate that they can lead to interesting phenomena. In particular, it has been shown that amphiphilic Janus nanoparticles can lead to cell membrane disruption, , anisotropically functionalized Janus nanoparticles offer extended cell surface attachment, and amphiphilic–polycationic Janus nanoparticles offer enhanced antibacterial activity . These results suggest that Janus nanoparticles with anisotropic functionalization have a wide range of application potentials that are yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Second, characterization of Janus structures at the <50 nm regime that occurs due to anisotropic surface chemistry and anisotropic functionalization is challenging due to the requirements of sophisticated chemical characterization at such length scales. Third, cellular interaction with Janus nanostructures is not well understood, and recent studies indicate that they can lead to interesting phenomena. In particular, it has been shown that amphiphilic Janus nanoparticles can lead to cell membrane disruption, , anisotropically functionalized Janus nanoparticles offer extended cell surface attachment, and amphiphilic–polycationic Janus nanoparticles offer enhanced antibacterial activity . These results suggest that Janus nanoparticles with anisotropic functionalization have a wide range of application potentials that are yet to be explored.…”
Section: Introductionmentioning
confidence: 99%